The game of academic publishing: a review of gamified publication practices in the social sciences - Köbli, Nathalie Ann; Leisenheimer, Luisa; Achter, Mira; Kucera, Teresa; Schadler, Cornelia (Frontiers in Communication, 2024)
In the last decades, academic publishing in the Social Sciences has experienced a shift towards research management by non-academic stakeholders and performance-based funding systems (PBFSs). The resulting conditions of knowledge production and dissemination are increasingly described with "game" metaphors. This article provides a literature review of research concerning publishing in the Social Sciences and discusses how gamification becomes a key element. Quantifying publication outcomes to assess and financially incentivize research performance results in a highly competitive playing field where access to goods and services is denied to those who play the game poorly. The pressure to publish leads to unethical behavior and predatory publishing which are two side-effects of gamified practices. The reviewed literature also shows unequal starting conditions in terms of gender and language inequalities, as well as the dominance of the Global North. We conclude that the gamification of publication practices in the Social Sciences leads to stressful and dreadful environments.There is a consensus that, particularly in the Social Sciences, publication cultures and requirements have changed over the past 50 years, substantially changing the way scholars work and write (Engels